A physical profile of elite female ice hockey players from the USA - Ransdell, L. B.; Murray, T. (The Journal of Strength and Conditioning Research, 2011)
Despite impressive numbers of hockey participants, there is little research examining elite female ice hockey players. Therefore, the purpose of this study was to describe the physical characteristics of elite female ice hockey players who were trying out for the 2010 US Women's Ice Hockey team. Twenty-three women participated in the study and were evaluated for body mass (kilograms), height (centimeters), age (years) vertical jump (centimeters), standing long jump (centimeters), 1RM front squat (kilograms), front squat relative to body mass (percent), 1RM bench press (kilograms), bench press relative to body mass (percent), pull-ups, and body composition (percent body fat). The athletes in this sample were 24.7 years of age (SD = 3.1) and 169.7 cm tall (SD = 6.9); on average, they weighed 70.4 kg (SD = 7.1) and reported 15.8% body fat (SD = 1.9). Mean vertical jump height was 50.3 cm (SD = 5.7) and standing long jump was 214.8 cm (SD = 10.9). Mean 1RM for the upper body strength (bench press) was 65.3 kg (SD = 12.2) (95.1 ± 15.5% of body mass), and 1RM for lower body (front squat) was 88.6 kg (SD = 11.2) (127.7 ± 16.3% of body mass). This study is the first to report the physical characteristics of elite female ice hockey players from the USA. Data should assist strength and conditioning coaches in identifying talent, testing for strengths and weaknesses, comparing future teams to these indicators, and designing programs that will enhance the performance capabilities of female ice hockey athletes.